1983
DOI: 10.1111/j.1469-185x.1983.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating System and Sexcul Dimorphism in Large Terrestrial, Mammalian Herbivores

Abstract: Summary Sexual dimorphism in mammals is not entirely satisfactorily explained by the models that are advanced to account for it among birds. This may be because species‐specific styles of being dimorphic, and of attaining mature dimorphic state, are not clearly recognized. Mature dimorphism is a syndrome involving body size, appearance and weaponry; each facet and the whole syndrome may have functions in both fighting and signalling. The mature dimorphic stage has to be reached by growth and change from juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
248
2
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(259 citation statements)
references
References 56 publications
8
248
2
1
Order By: Relevance
“…The few exceptions are in species in which roles may be partially mixed and the sexes have less notable differences, and which more often have mating systems characterized as monogamous (Jarman 1983, Plavcan 2001. The primate order includes a relatively large number of monogamous species, often characterized by some level of male parental investment (Fuentes 1998).…”
Section: Biological Theories About Human Gendermentioning
confidence: 99%
“…The few exceptions are in species in which roles may be partially mixed and the sexes have less notable differences, and which more often have mating systems characterized as monogamous (Jarman 1983, Plavcan 2001. The primate order includes a relatively large number of monogamous species, often characterized by some level of male parental investment (Fuentes 1998).…”
Section: Biological Theories About Human Gendermentioning
confidence: 99%
“…Moreover, as revealed by a comparative study in primates, male-male competition is also sensitive to the number of competitors, because male mating skew decreases as the number of males increases (Kutsukake and Nunn 2006). Importantly, as demonstrated for anthropoid primates, groups of up to five or six females can typically be monopolized by a single male (Mitani et al 1996;Nunn 1999), and these species tend to have the most pronounced sexual dimorphism (Alexander et al 1979;Jarman 1983;Plavcan 2001). Females may break this male monopolization by increasing their estrous synchrony (Nunn 1999), but a comparative study across primates found no relationship between the degree of male mating skew and the overlap in female receptivity (Kutsukake and Nunn 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in adult feeding are commonly linked to fluctuations in energetic and nutritional needs associated with sexual size dimorphism and costs of reproduction to females. Size dimorphism can have far reaching effects on growth, metabolism, and substrate or microhabitat use, as well as an individual's nutritional demands (Kleiber 1965;Fleagle and Mittermeier 1980;Jarman 1983;McGraw 1998;Beck et al 2005;O'Mara et al 2012). If size dimorphism is solely responsible for sex differences in feeding, then the divergence of female and male feeding ecology should parallel the developmental changes in size and strength (Jarman 1983;Watts 1988).…”
mentioning
confidence: 99%
“…If size dimorphism is solely responsible for sex differences in feeding, then the divergence of female and male feeding ecology should parallel the developmental changes in size and strength (Jarman 1983;Watts 1988). However, sexual dimorphism can also determine the priority of access to foods, with the larger or dominant sex more likely to exclude others from desired feeding patches (Jarman 1983;Ménard and Vallet 1986;Wan et al 2013). Sexbased social dominance can determine priority of access and sex differences in feeding could be imposed through harassment or monopolization by the dominant individuals (Barton and Whiten 1993;Bonanni et al 2007), particularly in the absence of sexual dimorphism (Overdorff et al 2005;White and Wood 2007;Smith et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation